USING FOLKTALE VIDEO AS A MEDIA TO TEACH WRITING NARRATIVE TEXT TO THE EIGHTH GRADERS (RETAIN, 2014)
USING FOLKTALE VIDEO AS A MEDIA TO TEACH WRITING NARRATIVE TEXT TO THE EIGHTH GRADERS Maya Septian Ningrum 102084222 English Education, Faculty of Languages and Art, State Universityof Surabaya email: mayasept@yahoo.com Dra. Theresia Kumalarini, M.Pd. English Education, Faculty of Languages and Art, State Universityof Surabaya email: kumala_rini52@yahoo.co.id Abstrak Mengingat menulismemerlukan beberapa prosedur dan bahwa tulisan yang baik mensyaratkan kriteria, dengan demikian, menulis adalah kegiatan yang sulit untuk dilakukan bagi sebagian siswa. Harmer ( 2012) menyatakan bahwa banyak siswa tidak begitumenikmati menulis, jadi tugas guru adalah untuk membuat mereka nyaman dan antusias dengan hal itu. Berkenaandenganitu, penggunaan video sebagai media audiovisual selalu menjadi bagian yang pentingdalammengatasi masalah tersebut. Menanggapiitu, penelitianinibertujuanuntukmenginvestigasipenggunaan video ceritarakyatdalamkegiatanmenulisteksnarasidanresponparasiswasetelahdiajardenganmenggunakan video yang diberikan. Observation checklist, catatanlapangan, dankuesionerdigunakanuntukmengumpulkan data yang diperlukandalampenelitiandeskriptifkualitatifini.Hasilpenelitianmenunjukkanbahwapenggunaan video ceritarakyatmengintegrasikankegiatanpre-viewing, viewing, and post-viewing. Hasilpenelitianjugamengungkapkanbahwaparasiswamemberirespon yang positifterhadappenggunaan video ceritarakyattersebut. Sekalipundemikian, Sekalipundemikian, menggunakan video dalam kelas harus disiapkan dengan baik oleh para guru. Mereka dapat menggunakan berbagai kegiatan tindak lanjut untuk memaksimalkan penggunaan video itu sendiri. Dengan demikian, hasil belajar yang optimal dapat dicapai oleh siswa. Kata Kunci: menulis, video, ceritarakyat, teksnarasi. Abstract Considering that writing employs some procedures and that of a good writing needs criterion, thus, writing is a hard activity to do for some students. Harmer (2012) claims many students do not enjoy writing very much and so the teacher’s task is to make them comfortable and enthusiastic about it. Following this, the use of video as an audiovisual aid has always been an integral part overcome the problem mentioned. Coping with the above problem, this study aimed to find out the use of folktale video in writing narrative activity and the students’ responses after being taught by the video given. Observation checklist, field notes and questionnaire were employed in three observations to confirm the data needed under the descriptive qualitative research.The results pointed out that the use of folktale video to teach writing narrative text integrated pre-viewing, viewing, and post-viewing activities. The results also described that the students gave positive response toward the use of folktale video. However, using video in class should be prepared well by the teachers. They may use various follow-up activities to maximize the use of the video itself. Thus, the optimal learning outcome can be achieved by the students. Keywords:writing, video, folktale, narrative text INTRODUCTION As a lingua franca since the past century, English plays an important role as a communication tool in the area science and technology information. It is in line with Crystal (2003) who states English a medium of a great deal of the world’s knowledge, especially in such areas of science and technology. In addition, the rapid development of English as an informational language in educational sector is significantly increasing. Thus, it makes the mastery of English become essential for students. Following this, English Standard Competence 2006 states that English is a means of communication in oral and written form, especially in getting information, expressing idea, improving technology, science, and culture (Depdiknas, 2006). Knowing the important role to study English in today’s life, students need to be sufficiently equipped with English communication skills, both oral and written. In order to study English either as the second or foreign language, students make an effort to develop and integrate the four basic skills which are listening, speaking, reading, and writing. Writing as one of those four language skill is very important. As stated by Byrne (1979), writing is one of the language skills which are should be mastered by the students as the way to communicate. Communicating in writing involves procedural activities starting from planning, drafting, revising, and rewriting in order to discover and produce ideas and views. Thus, writing is seen as a medium for self-expression for communication and to discovery meaning to be used to give signal or information to others (Petty and Jensen, 1980). Indonesia has English Standard Competence to guide teachers to teach writing. The aim of teaching writing at junior high level is to express the meaning of interpersonal, ideational, textual become written form which has communicative purpose, structured text, and also the characteristic of the language itself (Depdiknas, 2006). Writing in junior high level takes part in genres of narrative, descriptive, procedure, recount, and report. Narrative is given to junior high level in order to make the students able to express a short monologue which concern to one’s personal experience or fantasy story. According to Finoza (2001), narration as a kind of writing which create story and combine human behavior in the events in chronological order which happens in the past. On the other hand, Keraf (1996) defines narrative as a composition which has two basic components, events and a link of time. Narrative text is simply telling story. It can be such stories like legend, myth, folktale, and fable. Its purpose is for amusing the reader or listener (Anderson and Anderson, 1997). Considering that writing employs some procedures, producing a coherent, fluent, extended piece of writing is probably the most difficult activity to do. In addition, writing clear sentence requires learning the rules of English grammar and mechanics as well as commas and other marks of punctuation. Thus, writing seems as a complex, cognitive process that requires sustained intellectual effort over a considerable period of time (White and Arndt, 1991). As consequence, many students do not enjoy writing very much (Harmer, 2012). He further confirms that it is the teacher’s task to make them comfortable and enthusiastic about it. So, when students are involved in writing activity, a teacher in language learning is asked to create the right condition to generate the students’ ideas and make much effort to create a nice learning atmosphere in order to achieve the optimal result. One well-known way to minimize the students’ difficulties in writing activity can be achieved by bringing video into the class. Harmer (2001) asserts that students would see language-in-use when video is given in a task. Video can be a facilitator for the students to see the language in operation. They have a chance to see language in use as well as they hear it. Stempleski and Tomalin (1990) also state that students feel their interest quicken when language is experienced in a lively way through television or video.Video which presents combination of picture and sound can present language more comprehensively than any other teaching medium. Further, Harmer (2001) points out that video can enhance simulation and build students’ creativity and ideas. It provides feedback when students watch and evaluate what they have in mind to be applied in their real life. In this study, the researcher uses folktale video. Folktale is a variety of narrative story which is spoken beyond generation. Watching video in a writing task can be followed up with note-taking about the plot that students saw on the video. They can also review setting and characters that are involved in. Students can review them based on the folktale video given. This activity will be encouraging for students where there are worksheets and related material for them to work with on their writing task (Harmer, 2001), Considering the positive contribution of video to the teaching writing, therefore, the researcher is highly motivated in conducting a study entitled “Using Folktale Video as a Media to Teach Writing Narrative Text to the Eighth Graders”. METHOD Research Design Since the aims of this study were to investigate the use of folktale video for teaching writing narrative text to the eighth graders and their responses after the video is being implemented, this study used descriptive qualitative research. According to Ary et. al. (2010), qualitative research is designed to obtain information concerning on how a researcher makes sense of interpreting human experiences at the time of the study through verbal narratives and observations rather than through numbers. Subjects The subjects of this study were the English teacher and the eighth graders of VIII-A SMP Muhammadiyah 17 Plus Surabaya. The subjects were selected since they had applied folktale video as a media to teach writing narrative text in the teaching and learning process. Instruments Research instruments were aimed to help the researcher get the data. In this study, the researcher used three instruments, i.e. observation checklist, field notes, and questionnaire. The observation checklist and field notes noted all activities that did by both teacher and students during the teaching and learning process, while the questionnaire was looking for information about the students’ responses toward the use of folktale video in the teaching writing narrative text. This questionnaire consisted of 8 questions with options a, b, c, and d. a and b indicated positive response, while c and d indicated negative response. Data Collection The steps of data collections are explained as follows: The researcher collected the data through observations in the classroom when the teaching writing of a narrative text to the eighth graders was being done using folktale video. The researcher used observation checklist and field notes to observe the activities during three-meeting observations. The researcher used artifact analysis in the form of questionnaire to provide information related to the students’ responses toward the use of folktale video in the teaching writing of a narrative text. This questionnaire was given at the end of the teaching and learning process on the last observation. Data Analysis There were three steps for the data analysis of this study: Identifying and describing the data. The researcher identified the data accurately based on the observation checklist, field notes, and questionnaire. Then, the data were described qualitatively. Analyzing the results. The data that have been identified were presented. Observation checklist, field notes, and the results of the students’ questionnaire were thoroughly analyzed to see the results. Interpreting conclusion. After finishing those two steps, the interpretation of all the data was drawn into a conclusion. RESULTS The Results of the Observations In each meeting of the observations, the teacher conducted activities, i.e. opening, main activity, and closing. On the opening activity, she began to start the lesson by greeting the students, introducing the objectives of the lesson and reviewing the previous material. On the main activity, she went to the viewing activity, namely pre-viewing, viewing, post-viewing that allowed the students to retain massive amount of information presented on the video. Those activities, however, were expected to make the students easier to gather ideas what to be written. While on the closing, the teacher prepared herself to go out of class. Nevertheless, she asked the entire that was learnt at the day before she went out. The Results of the Questionnaire Since option a and b indicated positive response, while options c and d indicate negative response, and that the students gave their option most on b, followed by a then c and d, in consequence, it can be concluded that most of the students gave positive responses that using folktale video in the classroom can be applied to teach writing of a narrative text. DISCUSSION The Discussion of the Observations Based on the results of the observations on the use of folktale video to teach writing of a narrative text, there were some points that could be further discussed. Those points were dealing with the teacher’s activities, the students’ activities, and the media used. Regarding the use of folktale video to teach writing of a narrative text, the teacher integrated viewing activities, namely: pre viewing, viewing and post viewing that allowed students to retain massive amount of information presented on the video. As Lonergan (1984) states that in using video, the teacher is demanded to have not only a skill to handle the equipment, but also a skill to use various techniques for facilitating the learners. Dealing with the students’ activity, the students were actively involved in the learning process. They responded every teacher’s instruction. They were seriously watching and note-taking when the video played. They answered the questions the teacher asked. They were discussing and proofreading between friends when they wrote. The media given helped the students to perform their writing easily with the right use of generic structure and language features. Thus, the media used was in accordance to the curriculum, that is junior high students were expected to be able to understand and create a narrative text based on its generic structure and language features (BSNP, 2006). The Discussion of the Questionnaire Based on the result of the students’ questionnaire, it was clear that using folktale video to teach writing of a narrative text got positive responses from the students. The video given was made them understand about the topic they learned. Thus, most of the students felt pleased and interested-in the use of the video. As Harmer (2001) confirms that students are showing their interest when they have chance to see and hear the language in use in a particular tasks. Further, considering that writing is perceived as a difficult activity to do, almost all of the students admitted that the use of video as a teaching media was very helpful for their writing activity. What was to be watched, heard and comprehended on the video made them easier get the ideas what to be written on their narrative text, as Chau (2003) states that video makes language more accessible for students by making it easier to integrate and contextualize writing activities. CONCLUSION AND SUGGESTIONS Conclusion In the teaching and learning process, the teacher integrated pre-viewing, viewing, and post-viewing activities that proposed to make the students retain massive amount of information presented on the video and minimize the students’ difficulties in writing activity. Besides, she gave comments and feedback for what they were writing. In addition, the data from the students’ questionnaire showed that the use of folktale video gave positive responses from the students. They admitted that video was very helpful for their writing activity. Suggestions The use of video in language teaching needed to be prepared well by the teachers. They may use various follow-up activities to maximize the use of the video itself. They should also consider the appropriateness of the video in terms of its suitability to the objectives of the lesson, to the availability of time, to the students’ level and interest in order to achieve the optimal learning outcome. Further, since teaching with video gave several benefits, another researcher is encouraged to conduct the study of using the other kinds of video to teach in listening, speaking, or reading activity which not only helps the students minimize difficulties but also develop their skill. REFERENCES Ary, Donald et. al. (2010). Introduction to Research in Education, Eighth Edition. Canada: Wadsworth. Brown, H. Douglas. (2001). Teaching by Principles: An Interactive Approach to Language Pedagogy. Second Edition. New York: A Pearson Education Company. Chau, E. (2003). Developing Beginner Language Skills Through Video. AMEP Conference. Coffin, Trisam P and Stephen, Slater. (1990). Literature in The Language Classroom. Ney York: Cambridge University Press. Harmer, Jeremy. (2001). The Practice of English Language Teaching: Third Edition Completely Revised and Updated. Edinburgh Gate: Pearson Education Limited. Harmer, Jeremy. (2012). Essential Teacher Kowledge: Core Concept in English Laguage Teaching. Edinburgh Gate: Pearson Education Limited. Heubener, Theodore. (1967). Audio-Visual Technique in Teaching Foreign Language. New York: New York University Press. BNSP. (2006). Standar Isi untukSatuanPendidikanDasardanMenengah: StandarKompetensidanKompetensiDasar SMP/MTs.Jakarta.